Description and Selection of Communication Services for Service Oriented Network Architectures - Khondoker, Rahamatullah; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2016)
The research focus of Rahamatullah Khondoker is on Future Internet Architectures, Network Security, Software-Defined Networking, and Network Function Virtualization. In his PhD thesis, the author tackles challenges of today$1 (Bs layered network architecture (such as TCP/IP protocol stack) which is inflexible. He proposes that the evolution of the network can be achieved by first, decoupling applications from the networks and second, selecting the best network or protocol automatically based on the applications$1 (Brequirements. With the provided language, applications are able to express their requirements, and networks expose their capabilities such that the most appropriate network and protocol are selected automatically. Contents Research Methodology and Scientific Contribution Background: Service Oriented Network Architectures Service Description Service Selection Benefits and Future Work Examples of Communication Services Target Groups Lecturers and Students of Computer Science and Communication Networks Readers working in these Fields The Author Rahamatullah Khondoker defended his Dr.-Ing. degree in Computer Science at the University of Kaiserslautern in Germany. Currently, he is doing his post-doc research at Fraunhofer Institute for Secure Information Technology (SIT) in Darmstadt, Germany.s
Research Methodology and Scientific Contribution -- Background: Service Oriented Network Architectures -- Service Description -- Service Selection -- Benefits and Future Work -- Examples of Communication Services.
Keywords: Computer science; Computer organization; Software engineering; Computers; Computer Science; Computer Systems Organization and Communication Networks; Software Engineering/Programming and Operating Systems; Information Systems and Communication Service; Electronic books